Family caregiver feelings of hospitalized adult patients: Integrative Review - Greice Schultz, Vania (2019)
The objective of this research was to identify the feelings of family caregivers of hospitalized adult patients referred to in scientific productions. It is an integrative review based on content analysis, as proposed by Bardin in the electronic databases (PubMed, Lilacs and Scielo), using the keywords "Feelings" "Family caregiver" "Hospital" and "Hospitalization" Results: the analysis of the 21 studies allowed us to discuss topics such as: psychological distress; care concerns; ambiguous feelings; and restrictions on social life. Final Considerations: The identification of the feelings of family caregivers of hospitalized adults can serve as a basis for the (re) planning of intervention and care actions carried out by health professionals, as well as the need to implement programs and protocols of action aimed at this audience.